Relationship of selection criteria to subsequent academic performance in an Australian undergraduate dental school. (24th September 2012) - Mercer, A.; Abbott, P. V.; Puddey, I. B.
Abstract In 1998, in addition to previous academic achievement, an aptitude test (UMAT) and a structured interview were introduced into selection for the Bachelor of Dental Science (BDSc), the undergraduate dental course at the University of Western Australia. The aim of this study was to determine the relationship between the combination of school‐leaver dental students' entry scores, some demographic characteristics and subsequent student performance in the undergraduate course. Three hundred and ninety‐eight school‐leavers who enrolled in the BDSc from 1999 through 2011 were studied. Regression models were constructed comprising entry scores, gender and age as predictors in relation to subsequent academic performance. The main outcome measure was the weighted average mark (WAM) for each of five academic year levels as well as results in specific units, defined as either 'knowledge' based or 'clinically' based. Of the variables studied, previous academic performance and female gender had the strongest relationship with yearly WAM for Years 1 through 4 and for both 'knowledge' based and 'clinically' based units. The interview score showed a strong relationship in the major clinical years and in a range of 'clinically' based units. UMAT scores were less consistent in relationship to WAM. These results support assessment through a highly structured interview together with prior academic achievement as an evidence‐based approach to selection of students for this undergraduate dental course.